PERBEDAAN INDEKS MASSA TUBUH PADA AKSEPTOR KB SUNTIK 1 DAN 3 BULAN - Rufaridah, Anne; Putri, Kurnia; Cumayunaro, Ayuro; Sidaria, Sidaria (Jurnal Endurance, 2017)
Injection method is the most widely used contractive because the usage are safe, simple, effective and practice as long as the high these acceptor it is certaily followed by complain of side effects such weight changes, the purpose study uses an analitic with cross sectional approach. The population where 188 people where the acceptor injection contraceptives the sample amounted to 33 clients in each acceptor of 1 and 3 month the data collection are demographic data and questionaire sheet and it was analyzed by paired t-test and independent t-test. The result of this study showed that most of then were totally weight gains wich the difference mean value between pretest and postest the acceptor KB of 1 month is 3,71 kg/m² the while a mean value of the acceptor 3 months is 5,10 kg/m² those means there were a change of impact on weight gains amoung the acceptor KB of 1 and 3 months. While the value of independent t-test showed p=0,021 (p>0,05). Baced on these results it can be concluded that there were significantly difference wight changes between and acceptor injectable contraceptives 1 and 3 month expecte.